Supportive Care in Pediatric Cancer: The Road to Prevention of Thrombosis - Ommen, C. Heleen van; Chan, Anthony K. C. (Seminars in Thrombosis and Hemostasis, 2014)
The survival rate of children with cancer has increased impressively to almost 80% over the last decades as a result of improved diagnostic procedures and multimodal treatment strategies. Therefore, it becomes more and more important to prevent mortality and morbidity of treatment-associated complications, including venous thromboembolism (VTE). VTE occurs predominantly in children with acute lymphoblastic leukemia, lymphoma, and sarcoma. Pathogenesis of thrombosis in children with cancer is multifactorial. Thrombosis develops due to a combination of the primary disease itself, chemotherapy and supportive care, associated complications, and inherited prothrombotic risk factors probably contributed to the development of thrombosis in these children. Mortality as a result of VTE is low, but both symptomatic and asymptomatic thrombosis cause significant morbidity to justify primary thromboprophylaxis in children with cancer. Identification of risk factors is important to develop predictive models to identify patients at highest risk of thrombosis. Due to variations in risk factors, these models should be tailored to treatment protocols and patient populations. Multicenter studies are needed to investigate which prophylactic strategies are effective and safe to prevent thrombosis in children with cancer.
Keywords: cancer; pediatrics; venous thromboembolism; thromboprophylaxis